Aspects Regarding the Impact of the Internet on the Society - MOISE, Adrian Cristian (Journal of Advanced Research in Law and Economics; Vol 5 No 2 (2014): JARLE Volume V, Issue 2(10), Winter 2014, 2017)
This study proposes to present and analyze some aspects related to the impact of the Internet on the society. The social impact of the Internet results following the carrying out of an analysis on the fundamental principles of Internet Law, the ratio between cybersecurity and human rights, the phenomenon of globalization of Internet, the main organizations involved in Internet governance as well as on the role of Internet on the sustainability of the society. Development of Internet caused various problems for the information society such as: spam, identity theft, viruses, infringement of rights of intellectual property, domain names, infrastructure problems regarding access and interconnectivity. These problems related to technical, management or public policies aspects show that Internet needs better governance in order to be able to control them. Internet led to the occurrence of a virtual space (cyberspace), where users present a specific behavior. Cyberspace began to interact with the real world in domains such as: fundamental rights and freedoms, right to private life, use of personal data.